The Northeast Greenland Margin: tectonic evolution - Hermann, Tobias (2013)
The Norwegian-Greenland Sea (NGS) is an area of increasing interest. Here, the North Atlantic Current continues the Gulf Stream into the NGS. The warm ocean current plays an important role for the world's climate and influences the environment of the global Earth system. Calculations of climate models for the future based on the tectonic evolution of the NGS in the past. Based on few geoscientific data, the tectonic evolution of the NGS and the NE Greenland margin remains controversial. In the summer of 2009, the Alfred Wegener Institute acquired geophysical data - two seismic refraction lines as well as gravity data, measured in parallel to the seismic refraction lines - along the NE Greenland margin (Boreas Basin and offshore Kong Oscar Fjord (KOF)) during the ARK-XXIV/3 expedition. In addition, further gravity data (Arctic Gravity Project) were available and used within this study. Summarising the results, we could develop crustal models for the Boreas Basin and offshore KOF, using the seismic refraction data and the gravity data. Furthermore, a complex 3D gravity model of the NE Greenland margin was calculated, using the crustal models and further published data as boundary conditions. Following our conclusions, the structure of thin oceanic crust (3 km crustal thickness, absence of oceanic layer 3) in the Boreas Basin and along the ultraslow spreading Knipovich Ridge is more heterogeneous than previously thought. For the accretion of 9 km thick oceanic crust offshore KOF, the rift history of NE Greenland (extensive rifting before continental breakup) is more important than higher mantle temperatures caused by the Iceland Hotspot. Therefore, the Iceland Hotspot has smaller influence on the oceanic crustal accretion than previously thought. This might be further indicated by a 3 km thick high-velocity lower crust below the continent-ocean transition zone of KOF which is formed by enhanced melt generation along the nearby Jan Mayen Fracture Zone.